PEMBANGUNAN EKONOMI DALAM PERSPEKTIF EKONOMI ISLAM - ALMIZAN ALMIZAN (Maqdis: Jurnal Kajian Ekonomi Islam, 2016)
The theme of the article is based on economic principles Islam. The purpose of research is to see economic development in the perspective of the Islamic economy. Research is the study of literature. Economic development is one of the strategies to achieve the goals aspired nation. The goal is how poverty, unemployment, economic disparity and social resolved so as to realize human welfare. But in fact, the construction of which is expected to have an influence on society has not caused yet siding with the people. Increased poverty and unemployment occur, ultimately requires all state elites to reformulate development strategies that are better suited to be applied in a country rich in natural resources. Thus, there is no society that neglected and underdeveloped. It is appropriate experts economic, social, technological and political start doing a lot of studies on how to make successful development without being haunted by their poverty and unemployment. economic development as the growth of human maturity, in which material progress is inevitable and must be supported by the power of spiritual maturity. An important goal of employment growth coupled with reliable and skilled in their fields, will be the quality of the work that has quality, economic stability, distributive justice and concern for nature. Economic development is comprehensive Islam has the characteristics of an element of spiritual, moral, and material, and activities tend to be multidimensional so that all business submitted to balance a variety of factors and does not cause inequality.